MEROMORPHIC FUNCTIONS THAT SHAREONE VALUE WITH ITS FIRST DERIVATIVE - Al-Khaladi, Amer (Iraqi Journal of Science, 2024)
In this paper we study the uniqueness of meromorphic functions that share onevalue only with their derivatives. The results here are improved for the results in [1]and also we gave answer for open question in our paper.